Sex, Diastolic Blood Pressure, and Outcome after Thrombolysis for Ischemic Stroke - David Nathanson; Cesare Patrone; Thomas Nyström; Mia von Euler (Stroke Research and Treatment)
Background. The goal of this study was to identify differences in risk factors and functional outcome between the two sexes in patients treated with thrombolysis for ischemic stroke. Methods. This cohort study audited data from patients treated with thrombolysis for ischemic stroke during a 3-year period at Södersjukhuset, Stockholm. Results. Of the 355 patients included in the study, 162 (45%) were women and 193 (54%) were men. Women were older with a median age of 76 years; median age for men was 69 years (P<0.0001). Diastolic blood pressure was lower for women compared to men (P=0.001). At admission fewer women had a favorable modified Rankin Scale score compared to men (93.8% versus 99%, P=0.008). Three months after discharge functional status did not differ significantly between the two sexes. Diastolic blood pressure was associated to functional outcome only in men when sex specific odds ratios were calculated (OR, 5.7; 95% CI, 1.7–20). Conclusion. The study indicates that females appear to gain a relatively greater benefit from thrombolytic therapy than men due to a better functional recovery. A higher diastolic blood pressure increases the risk for a worse prospective functional status in men.